Induction of citrate transporter gene expression in soybean roots by sulfur application. Issue 5 (2nd November 2022) - Sugiura, Hinako; Miyaji, Shunsuke; Yamamoto, Saki; Yasuda, Michiko; Damo, Jean Louise Cocson; Ramirez, Maria Daniela Artigas; Agake, Shin-Ichiro; Kamiya, Takehiro; Fujiwara, Toru; Bellingrath-Kimura, Sonoko Dorothea; Tanaka, Haruo; Sugihara, Soh; et al.
ABSTRACT: Organic acid secretion from the roots enables plants to acquire phosphorus (P) which is poorly soluble in soil. We previously reported that when soybeans were cultivated in vermiculite in the presence of insoluble calcium phosphate, as a phosphorus source, sulfur (S) fertilization increased organic acid secretion from the roots and improved P acquisition in soybeans. In the present study, we confirmed that S fertilization increased secretion of organic acids such as citric acid when soybeans were cultivated in Andosols having a strong P fixation capacity. In contrast, concentration of citric acid in soybean roots did not increase by S fertilization. Therefore, the relationship between S nutrition and gene expression of citric acid exporters was investigated to understand the mechanisms of induction of citric acid secretion by S. Further, we verified whether the expression of citric acid transporter genes, GmMATE13 and GmMATE47, is involved in the induction of citric acid secretion from the roots by S fertilization. The expression level of GmMATE13 in roots was significantly increased by S fertilization compared to that without S fertilization. Therefore, our results suggest that S nutrition is involved in inducing GmMATE13 expression and contributes to the excretion of citric acid from the soybean roots.